(untitled) (Archives of Clinical Psychiatry, 2015)
Background The body-checking is a frequent behavior observed in young adults. It is associated with body dissatisfaction and inappropriate eating attitudes. However, its association with nutritional status remains unclear. Objectives This study aimed to assess the association between body-checking behavior and nutritional status. Methods We conducted a cross-sectional study with 587 (311 men) undergraduate students from the city of Juiz de Fora – Minas Gerais. The frequency of body-checking behavior was assessed by Body Checking Questionnaire and Male Body Checking Questionnaire; and inappropriate eating attitudes by Eating Attitudes Test-26. Body weight and height were self-reported. Descriptive, Chi-square test of association and Multiple Correspondence Analysis were done, adopting a statistical significant level of 5%. Results Association was found between body-checking behavior, nutritional status and gender (c2 (64) = 3219.88; p < 0.001). The Multiple Correspondence Analysis demonstrated association between the nutritional status categories low weight, eutrophia and overweight conjointly with low and moderate body-checking categories. Obesity and high body-checking, in turn, were inversely associated. Discussion There was an association between nutritional status and the frequency of body-checking behaviors in young adults of both genders. Body-checking is a behavior that deserves attention and monitoring in epidemiological and clinical practices.